Estimating the effect of vaccination on antimicrobial-resistant typhoid fever in 73 countries supported by Gavi: a mathematical modelling study. Issue 5 (May 2022) - Birger, Ruthie; Antillón, Marina; Bilcke, Joke; Dolecek, Christiane; Dougan, Gordon; Pollard, Andrew J; Neuzil, Kathleen M; Frost, Isabel; Laxminarayan, Ramanan; Pitzer, Virginia E
Summary: Background: Multidrug resistance and fluoroquinolone non-susceptibility (FQNS) are major concerns for the epidemiology and treatment of typhoid fever. The 2018 prequalification of the first typhoid conjugate vaccine (TCV) by WHO provides an opportunity to limit the transmission and burden of antimicrobial-resistant typhoid fever. Methods: We combined output from mathematical models of typhoid transmission with estimates of antimicrobial resistance from meta-analyses to predict the burden of antimicrobial-resistant typhoid fever across 73 lower-income countries eligible for support from Gavi, the Vaccine Alliance. We considered FQNS and multidrug resistance separately. The effect of vaccination was predicted on the basis of forecasts of vaccine coverage. We explored how the potential effect of vaccination on the prevalence of antimicrobial resistance varied depending on key model parameters. Findings: The introduction of routine immunisation with TCV at age 9 months with a catch-up campaign up to age 15 years was predicted to avert 46–74% of all typhoid fever cases in 73 countries eligible for Gavi support. Vaccination was predicted to reduce the relative prevalence of antimicrobial-resistant typhoid fever by 16% (95% prediction interval [PI] 0–49). TCV introduction with a catch-up campaign was predicted to avert 42·5 million (95% PI 24·8–62·8 million) cases and 506 000 (95% PI 187 000–1·9 million) deaths caused by FQNS typhoid fever, and 21·2 million (95% PI 16·4–26·5 million) cases and 342 000 (95% PI 135 000–1·5 million) deaths from multidrug-resistant typhoid fever over 10 years following introduction. Interpretation: Our results indicate the benefits of prioritising TCV introduction for countries with a high avertable burden of antimicrobial-resistant typhoid fever. Funding: The Bill & Melinda Gates Foundation.